Combined HIIT and Resistance Training in Very Long-Chain Acyl-CoA Dehydrogenase Deficiency: A Case Report - Herrera-Olivares, Alba M.; Fernández-Luque, Jose A.; Paradas, Carmen; Lucia, Alejandro; Santalla, Alfredo (Frontiers in Physiology, 2019)
Very long-chain acyl-CoA dehydrogenase deficiency (VLCADD) is a rare disorder of mitochondrial fatty acid -oxidation characterized by a spectrum of clinical manifestations. Patients with the adult-onset form can present with muscle pain, rhabdomyolysis and myoglobinuria after physiological stress, such as fasting and exercise. We report on a 23-year-old female patient with a history of recurrent rhabdomyolysis. The patient completed a 6-month supervised combined (aerobic + resistance) training program, with the addition of a medium chain triglyceride + carbohydrate supplement provided 60 min before each session. Aerobic training consisted of 6 sets of 70–80 s high-intensity interval training (HIIT) performed at maximum intensity with a minimum cadence of 100 rpm. Resistance training consisted of a circuit of basic exercises with dumbbells and elastic bands, with sets of 4–7 repetitions. The patient was evaluated at months 0, 3 and 6 using an incremental discontinuous step protocol, with steps of 1 min of exercise / 1 min of passive recovery, at a high pedal cadence. The test started at 10 W, with a load increase of 10 W / step. Blood creatine kinase (CK) concentration was measured before each evaluation. Training induced increments of 90.2% in peak oxygen uptake (VO2peak), 71.4% in peak power output and 24.7% in peak heart rate. The patient reported no muscle pain, contractures, rabdomyolysis (basal CK concentration was always < 200 U/L) or hospital admissions during the training period. After completion of 6-month program, the patient remained active, doing similar but non-supervised training for 1.5 years (to date). During this period, the patient has not reported myalgias, contractures, rhabdomyolysis or hospital admissions. Our preliminary data suggest that it is possible to carry out a combined (aerobic + strength) training program in patients with VLCADD, safely (without muscle contractures or rhabdomyolysis) and obtaining high values of VO2peak and cycling power output.